A mechanical property evaluation of graded density Al-Si10-Mg lattice structures manufactured by selective laser melting - Maskery, Ian; Aboulkhair, N.T.; Aremu, Adedeji; Tuck, Christopher; Ashcroft, Ian; Wildman, Ricky D.; Hague, Richard J.M. (Elsevier, 2016)
Metal components with applications across a range of industrial sectors can be manufactured by selective laser melting (SLM). A particular strength of SLM is its ability to manufacture components incorporating periodic lattice structures not realisable by conventional manufacturing processes. This enables the production of advanced, functionally graded, components. However, for these designs to be successful, the relationships between lattice geometry and performance must be established. We do so here by examining the mechanical behaviour of uniform and graded density SLM Al-Si10-Mg lattices under quasistatic loading. As-built lattices underwent brittle collapse and non-ideal deformation behaviour. The application of a microstructure-altering thermal treatment drastically improved their behaviour and their capability for energy absorption. Heat-treated graded lattices exhibited progressive layer collapse and incremental strengthening. Graded and uniform structures absorbed almost the same amount of energy prior to densification, 6.3±0.26.3±0.2 MJ/m3 and 5.7±0.25.7±0.2 MJ/m3, respectively, but densification occurred at around 7% lower strain for the graded structures. Several characteristic properties of SLM aluminium lattices, including their effective elastic modulus and Gibson-Ashby coefficients, C1 and α, were determined; these can form the basis of new design methodologies for superior components in the future.